Effective treatment of solitary rectal ulcer syndrome using argon plasma coagulation - Waniczek, Dariusz; Rdes, Jerzy; Rudzki, Marek K.; Piecuch, Jerzy; Rubicz, Nina; Arendt, Jerzy (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Solitary rectal ulcer syndrome (SRUS) is a chronic, multiform, non-cancerous disorder of the rectum, the final diagnosis of which is based upon histopathological criteria. This disorder is often accompanied by latent proctoptosis. We present a patient who (in 1996) was the first case in which argon plasma coagulation (APC) was used for SRUS treatment. In the years 2004–2005 the same patient underwent 15 APC sessions (at monthly intervals) obtaining full recovery from SRUS, although she had been treated unsuccessfully for 17 years prior to that. Six-year observation did not show any relapse. Local therapy with APC seems to be an important alternative in SRUS treatment without prolapse of the rectum and could become a basic method for bleeding treatment in SRUS.